An observational study of the timing of surgery, use of laparoscopy and outcomes for acute cholecystitis in the USA and UK - Murray,AC; Markar,S; Mackenzie,H; Baser,O; Wiggins,T; Askari,A; Hanna,G; Faiz,O; Mayer,E; Bicknell,C; Darzi,A; Kiran,RP (Surgical Endoscopy, 2018)
BACKGROUND: Evidence supports early laparoscopic cholecystectomy for acute cholecystitis. Differences in treatment patterns between the USA and UK, associated outcomes and resource utilization are not well understood. METHODS: In this retrospective, observational study using national administrative data, emergency patients admitted with acute cholecystitis were identified in England (Hospital Episode Statistics 1998-2012) and USA (National Inpatient Sample 1998-2011). Proportions of patients who underwent emergency cholecystectomy, utilization of laparoscopy and associated outcomes including length of stay (LOS) and complications were compared. The effect of delayed treatment on subsequent readmissions was evaluated for England. RESULTS: Patients with a diagnosis of acute cholecystitis totaled 1,191,331 in the USA vs. 288 907 in England. Emergency cholecystectomy was performed in 628,395 (52.7% USA) and 45,299 (15.7% England) over the time period. Laparoscopy was more common in the USA (82.8 vs. 37.9%; p < 0.001). Pre-treatment (1 vs. 2 days; p < 0.001) and total ( 4 vs. 7 days; p < 0.001) LOS was lower in the USA. Overall incidence of bile duct injury was higher in England than the USA (0.83 vs. 0.43%; p < 0.001), but was no different following laparoscopic surgery (0.1%). In England, 40.5% of patients without an immediate cholecystectomy were subsequently readmitted with cholecystitis. An additional 14.5% were admitted for other biliary complications, amounting to 2.7 readmissions per patient in the year following primary admission. CONCLUSION: This study highlights management practices for acute cholecystitis in the USA and England. Despite best evidence, index admission laparoscopic cholecystectomy is performed less in England, which significantly impacts subsequent healthcare utilization.